Did androgen-binding protein paralogs undergo neo- and/or Subfunctionalization as the Abp gene region expanded in the mouse genome? - Robert C Karn; Amanda G Chung; Christina M Laukaitis (PLoS ONE)
The Androgen-binding protein (Abp) region of the mouse genome contains 30 Abpa genes encoding alpha subunits and 34 Abpbg genes encoding betagamma subunits, their products forming dimers composed of an alpha and a betagamma subunit. We endeavored to determine how many Abp genes are expressed as proteins in tears and saliva, and as transcripts in the exocrine glands producing them. Using standard PCR, we amplified Abp transcripts from cDNA libraries of C57BL/6 mice and found fifteen Abp gene transcripts in the lacrimal gland and five in the submandibular gland. Proteomic analyses identified proteins corresponding to eleven of the lacrimal gland transcripts, all of them different from the three salivary ABPs reported previously. Our qPCR results showed that five of the six transcripts that lacked corresponding proteins are expressed at very low levels compared to those transcripts with proteins. We found 1) no overlap in the repertoires of expressed Abp paralogs in lacrimal gland/tears and salivary glands/saliva; 2) substantial sex-limited expression of lacrimal gland/tear expressed-paralogs in males but no sex-limited expression in females; and 3) that the lacrimal gland/tear expressed-paralogs are found exclusively in ancestral clades 1, 2 and 3 of the five clades described previously while the salivary glands/saliva expressed-paralogs are found only in clade 5. The number of instances of extremely low levels of transcription without corresponding protein production in paralogs specific to tears and saliva suggested the role of subfunctionalization, a derived condition wherein genes that may have been expressed highly in both glands ancestrally were down-regulated subsequent to duplication. Thus, evidence for subfunctionalization can be seen in our data and we argue that the partitioning of paralog expression between lacrimal and salivary glands that we report here occurred as the result of adaptive evolution.